Yupana Inka Tawa Pukllay arithmetic eye tracking analysis: novices - Guzman-Jimenez, Rosario; Prem, Dhavit; Saldívar, Alvaro; Escotto-Córdova, Eduardo Alejandro (Frontline Learning Research, 2025)
The concept of number emerges from the interaction of psychological, behavioral, and material elements of numerical cognition, collapsing the distinction between "abstract" and "concrete." This dual nature is evident in the Inca numerical system, where tools like the yupana integrate abstract numerical concepts with concrete materials. The Yupana Inka Tawa Pukllay (YITP), a Peruvian arithmetic method, enhances mathematical and visual-spatial skills through tile-based board games. While effective with children, its impact on university students is unexplored. This research used eye tracking to study gaze and attention during YITP operations, comparing novices and experts. Eight university students and two experts participated, with eye-tracking data and scatter plot (dispersion plot) analyses collected using Tobii Pro Glasses. The study introduced the Variation Ratio Tokens (VRT) metric to assess visual attention efficiency, showing significant improvements in VRT dispersion and attention during the arithmetic learning process. These findings suggest YITP’s potential in higher education for improving cognitive processes and arithmetic performance, laying a foundation for future research and innovative educational practices. This work establishes a foundation for cross-cultural cognitive studies and innovative STEM education approaches leveraging ancestral knowledge systems.